Ketiadaan Mutlak dalam Buddhisme Zen Perspektif Pemikiran Nishida Kitarō dan Korelasinya dengan Realitas - Fattah, Galuh Nur; Tangrestu, Venessya (Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
This essay discusses Nishida Kitarō's view of absolute nothingness, a concept influenced by the tradition of Zen Buddhism. Methodologically, it is designed as philosophical hermeneutics and aims to provide a new perspective in the study of philosophy. Nishida's thinking is based on the tradition of Western philosophical thought, especially Hegel, Kant, and Heidegger. However, in its development, Nishida created a new philosophical construction that attempted to criticize the Western philosophical tradition. This paper shows that Nishida Kitarō internalized Zen Buddhism into his philosophy. Nishida brings together Zen Buddhism as a philosophical thought with various types of thought and figures in the Western philosophical tradition. Zettai mu or absolute nothingness is at the heart of all of Nishida's metaphysical edifice. This absolute nothingness is built on a spatial logic that allows contact between the subject and the object. Nishida understands the concept of absolute nothingness in three phenomenologies of personal identity. These three stages lead to the contradiction of absolute self-identity. These findings can contribute to forming new enlightenment in freeing oneself from false perceptions of reality and wrong views.